Sussex Integrated Dataset (SID) Data Resource Profile - Ford, Elizabeth; Elsom, Jon; Molyneux, Paul; Crees, David; Bakare, Yemisi; Hughes , Dan (International Journal of Population Data Science, 2026)
This paper presents a data resource profile of the Sussex Integrated Dataset (SID). SID is a linked dataset of National Health Service (NHS) and adult social care data from across the geographical footprint of Sussex, in coastal Southeast England, and represents around 1.7 million patients. Living in a predominantly rural and coastal area, the population has more elderly people than the national average and is characterised by large differences in deprivation levels particularly in coastal towns. The city of Brighton and Hove has a large LGBTQ+ population and the largest cohort of people living with HIV outside of London. First linked in 2019, the dataset contains contributions from all NHS providers across East and West Sussex and the city of Brighton and Hove, including routinely collected data from all Sussex hospital trusts, general practitioners (up to 100% coverage), community and mental health trusts, ambulance data and local authority social care services. Most data sources provide information from 2017, with general practice data going back up to 20 years. Data quality is carefully monitored, demographics are harmonised within a "demographic milestones" table, and patient cohorts living with common long-term conditions are curated using a "semantic layer". Already used widely within NHS Sussex and by Local Authorities for public health, service evaluation, monitoring and planning, the SID is available more widely to use for research and innovation through the NHS Secure Data Environment Network.